ANALYSIS RISK FACTORS FOR NECK PAIN COMPLAINTS IN PRODUCTION WORKERS AT PT MARUKI INTERNATIONAL INDONESIA - Naurah Nadhifah; Irianto Irianto; A. Besse Ahsaniyah (Faculty of Medicine, Hasanuddin University., 2019)
Intorduction: The current most frequent health problem is Musculoskeletal Disorder (MSDs), which is pain in the neck muscles. Neck pain is a complaint taken at the back of the upper spine or cervical. Many factors affect neck pain. This study aims to determine the relationship of each risk factors with neck pain.Methods: This research was a descriptive cross sectional study involving 43 respondents based on the purposive sampling method. Risk factors taken were age, sex, years of service, work attitude, equality of shoulder height, and work posture measurements using Hand Arm Risk-Assesment Method (HARM)) and using the Visual Analog Scale (VAS) to assess the level of neck pain.Results: Data analysis using spearman with a value of p < 0.05 for years of service and work posture and the others factors with a value of p > 0.05 for sex, age, work attitude and equality of shoulder height that showed there was not significant relationship between gender, age, work attitude and equality of shoulder height with neck pain.Conclusion: There was a significant relationship between years of service and work posture with neck pain and there was not significant relationship between gender, age, work attitude and equality of shoulder height with neck pain.